TRANSLATION TECHNIQUES OF PHRASEOLOGICAL UNITS IN JOURNALISTIC TEXTS (SPANISH-PORTUGUESE) - Silva Santos, Flavia Andressa da [UNESP]; Garcia Simao, Angelica Karim [UNESP] (Univ Federal Santa Catarina, Nucleo Traducao, 2015)
This article aims to discuss the translation of phraseological units contained in a parallel bilingual corpus (Spanish-Portuguese) composed of journalistic texts taken from El Pais, Spanish newspaper, and their respective translations into Brazilian Portuguese published on UOL website (News/International) in January 2011. The analysis has as focus translation strategies and techniques used, as well as possible meaning effects observed in the target text. Thus, the reflection herein proposed discusses and is founded on the concepts of translation method, strategies, and techniques, situating our analysis in the field between Translation Studies and Bilingual Phraseology. Such perspective understands Translation as a communicative, textual and cognitive process, and phraseological units as lexical units made up of more than two graphic words in their lower limit, whose upper limit is located at the compound clause level. The translation analysis displayed the emptying of senses proposed in the source texts due to an excessive use of literal translations instead of well-known equivalents in the target language.
Keywords: Translation techniques; Bilingual phraseology; Journalistic text; Spanish language